Turning the lens in the study of precarity: On experimental social psychology's acquiescence to the settler‐colonial status quo in historic Palestine. (9th November 2022) - Hakim, Nader; Abi‐Ghannam, Ghina; Saab, Rim; Albzour, Mai; Zebian, Yara; Adams, Glenn
Abstract: This review examines the coloniality infused within the conduct and third reporting of experimental research in what is commonly referred to as the 'Israeli‐Palestinian conflict'. Informed by a settler colonial framework and decolonial theory, our review measured the appearance of sociopolitical terms and critically analysed the reconciliation measures. We found that papers were three times more likely to describe the context through the framework of intractable conflict compared to occupation . Power asymmetry was often acknowledged and then flattened via, for instance, adjacent mentions of Israeli and Palestinian physical violence. Two‐thirds of the dependent variables were not related to material claims (e.g. land, settlements, or Palestinian refugees) but rather to the feelings and attitudes of Jewish Israelis and Palestinians. Of the dependent measures that did consider material issues, they nearly universally privileged conditions of the two‐state solution and compromises on refugees' right of return that would violate international law. The majority of the studies sampled Jewish–Israeli participants exclusively, and the majority of authors were affiliated with Israeli institutions. We argue that for social psychology to offer insights that coincide with the decolonization of historic Palestine, the discipline will have to begin by contextualizing its research within the material conditions and history that socially stratify the groups.